Mobile health-based digital intervention to improve ARV compliance and nutritional intake in PLHIV at Bandarharjo Health Center - Rahayu Winarti; Rozaq Isnaini Nugraha; Iq Balurrochman; Nanang Bagus Setiawan; Niken Sukesi (AcTion: Aceh Nutrition Journal, 2025)
Low adherence to antiretroviral (ARV) therapy and inadequate nutritional intake remain persistent challenges among People Living with HIV/AIDS (PLHIV) in Indonesia, contributing to suboptimal treatment outcomes and reduced quality of life. Mobile health (mHealth), which utilizes mobile devices for health interventions, offers a promising solution by facilitating personalized, accessible, and continuous patient support. This study aimed to assess the effectiveness of an Android-based mHealth application, SEHAT+, in improving ARV adherence and nutritional intake among PLHIV at the Bandarharjo Health Center, Semarang. A total of 41 active PLHIV undergoing ARV therapy were recruited from March to May 2025. Descriptive and paired t-test analyses were conducted to compare adherence and intake before and after the intervention. The mean ARV adherence score increased from 62,3 (SD = 10,5) to 84,9 (SD = 8,1), and the nutritional intake score improved from 58,7 (SD = 11,2) to 79,2 (SD = 9,6), both showing statistically significant changes (p < 0,001). SEHAT+ features included medication reminders, dietary logs, multimedia-based nutrition education, and online consultation forums. The findings indicate that mHealth interventions can significantly enhance both medication compliance and nutritional behavior in PLHIV. Community-driven digital tools such as SEHAT+ have the potential to strengthen primary healthcare responses to HIV/AIDS in resource-constrained settings.